PENGARUH POLA PEMBIMBINGAN ORANG TUA TERHADAP CAPAIAN KOMPETENSI KOGNITIF DAN AFEKTIF SISWA SD KELAS RENDAH PADA MASA BELAJAR DARI RUMAH - Nor Akhlis; Hari Wahyono; Siti Aisyah (ITB AAS INDONESIA Surakarta, 2022)
The aims of this research were (1) to determine the effect of parental guidance patterns on the achievement of low-grade students' cognitive and affective competencies during the study period from home (2) how much the influence of parental guidance patterns have on the achievement of low-grade students' cognitive and affective competencies during learning from home. This study uses quantitative research methods. The population of this study were 1.096 students A sample of 284 students was taken. The research instrument used was a random sampling. The data analysis method used a questionnaire, and data analysis using the Parson model correlation. Based on the results of the analysis (1) is the best mentoring pattern during learning from home, (2) The pattern of parental guidance partially affects the achievement of cognitive competence of low-grade elementary school students during learning from home. This is based on the results of the t-test that the value of tstatistic > ttable (13.375 > 1.976) or a significance value of